2015
DOI: 10.3109/07420528.2015.1073158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial light at night on human health: A literature review of observational and experimental studies applied to exposure assessment

Abstract: It has frequently been reported that exposure to artificial light at night (ALAN) may cause negative health effects, such as breast cancer, circadian phase disruption and sleep disorders. Here, we reviewed the literature assessing the effects of human exposure to ALAN in order to list the health effects of various aspects of ALAN. Several electronic databases were searched for articles, published through August 2014, related to assessing the effects of exposure to ALAN on human health; these also included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
235
1
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(258 citation statements)
references
References 97 publications
6
235
1
16
Order By: Relevance
“…This diversity may be linked to morbidity of metabolic diseases, mental health issues, and cancer (1)(2)(3)(4). As dietary conditions have changed in modern society, delay in mealtimes and increases in dietary fat content have become more frequent.…”
Section: Abstract the Effects Of Dietary And Lighting Conditions On mentioning
confidence: 99%
“…This diversity may be linked to morbidity of metabolic diseases, mental health issues, and cancer (1)(2)(3)(4). As dietary conditions have changed in modern society, delay in mealtimes and increases in dietary fat content have become more frequent.…”
Section: Abstract the Effects Of Dietary And Lighting Conditions On mentioning
confidence: 99%
“…In the modern world, artificial light confers a number of social and economic benefits. However, exposure to light during the biological night has been linked to a number of physiological disturbances that may negatively affect health (1,2).…”
mentioning
confidence: 99%
“…A number of epidemiological studies have shown that shift workers are at increased risk of acute and chronic health effects (2,3), which are directly or indirectly related to exposure to LAN (1).…”
mentioning
confidence: 99%
“…• elle réduit la visibilité du ciel étoilé (Falchi et al, (2016) • elle a des effets sur l'Homme quant à la production des hormones et à son cycle biologique, avec probablement des impacts plus larges sur sa santé (Cho et al, 2015),…”
unclassified